Genesis of copper oxide nanoparticles from waste printed circuit boards and evaluation of their photocatalytic activity - Gautam P.; De A.K.; Sinha I.; Behera C.K.; Singh K.K. (My University, 2025)
Discarded Printed Circuit Boards (PCBs) are one of the secondary resources of high-purity copper, and precious materials, which if disposed off inappropriately may present several environmental risks. This study focuses on the production of copper oxide nanoparticles (CuO NPs) from reclaimed copper via a facile precipitation route to obtain a value-added nanoproduct. The synthesis involved the dissolution of downsized PCBs, leaching of Cu into the solution phase and the precipitation of nanoparticles (NPs) in an alkaline medium. XRD analysis confirmed the as-synthesized NPs were monoclinic CuO of size 19.23 nm without any impurity. HRTEM analysis confirmed that the NPs were nearly round spheres with average particle size of 19.973 ± 6.036 nm. The NPs have a specific surface area of 200 m2/g and mesoporous structure with mean pore diameter of 18.051 nm. The CuO NPs photocatalyzed the degradation of Congo Red under visible light irradiation. Hence, the PCB e-waste was utilized to produce nanomaterials with added-values, decreasing environmental problems. © 2023 Elsevier Inc.